RNAi therapy with givosiran significantly reduces attack rates in acute intermittent porphyria. (23rd January 2022) - Sardh, Eliane; Harper, Pauline
Abstract: Acute hepatic porphyria (AHP) is a group of inherited metabolic disorders that affect hepatic heme biosynthesis. They are associated with attacks of neurovisceral manifestations that can be life threatening and constitute what is considered an acute porphyria attack. Until recently, the sole specific treatment for acute porphyria attacks consisted of the intravenous administration of hemin. Although attacks are often sporadic, some patients develop recurrent acute attacks, with devastating effects on quality of life. Liver transplantation has historically been the sole curative treatment option. The clinical manifestations of AHP are attributed to the accumulation of the heme precursor 5‐aminolevulinic acid (ALA) and porphobilinogen (PBG). Advances in molecular engineering have provided new therapeutic possibilities for modifying the heme synthetic pathway. We reviewed the background and current status of AHP treatment using liver‐directed small interfering RNA targeting ALAS1 . The therapeutic aim was to normalize the levels of ALAS1, which is highly upregulated during acute porphyria attacks. Givosiran is now an approved drug for use in adults and adolescents aged 12 years and older. The results of clinical trials have shown that givosiran treatment leads to a rapid and sustained reduction of ALAS1 mRNA, decreased heme precursor levels, and a decreased rate of acute attacks compared with placebo. The clinical trials (phases I, II, and III) were all randomized and placebo controlled. Many patients enrolled in the initial clinical trials have continued treatment in open label extension and extended/compassionate‐use programs in countries where givosiran is not yet commercially available. Abstract :